SISTEM INFORMASI E-BUSINESS PRODUK THERASKIN BERBASIS WEB (STUDI KASUS EVI SHOP) - Widiani, Susi; Kasmi, Kasmi; Roziq Roihansyah, Dlofa (YHMM PUBLISHING, 2025)
This research addresses the challenges faced by Evi Shop, a business specializing in the sale of Theraskin products, where traditional methods of promotion and transaction-such as printed media and offline events-have become less effective due to increasing customer demand. To overcome this problem, the study aims to develop a web-based E-Business Information System in the form of an online store that streamlines transactions, promotions, and product ordering. The system development follows the Waterfall method, encompassing stages such as system analysis, design, implementation, operation, and maintenance. Data collection methods include observation, interviews, and literature review. The website application is developed using PHP as the programming language, Dreamweaver for interface design, and MySQL as the database. The result shows that the newly developed system significantly improves the efficiency and effectiveness of transaction and promotion processes. It also enhances customer convenience by enabling online purchasing and supports the business in expanding its market reach. This system is expected to contribute positively to the digital transformation of small businesses like Evi Shop, while also offering added value to customers through easier access to skincare products online.